Strength and stress-strain parameters from a constitutive hardening soil model for settlement analysis of strip footings - Ventura, Giancarlo P.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Back in 1970, Duncan and Chang developed a hyperbolic stress-strain relationship for analyses of stresses and displacements of soil masses. However, in order to accurately perform these analyses, the stress-strain characteristics of the soil must be realistically represented. The difficulty in modeling soil arises from the fact that the stress-strain characteristics of soils are non-linear, inelastic, and highly dependent on the stresses in the soil. Modeling this complex behavior of soil was addressed in this research by formulating equations in the framework of an elasto-plastic constitutive Hardening Soil Model derived from the hyperbolic material parameters determined from drained and undrained tri-axial tests of the Duncan and Chang Model. The obtained strength and stiffness/stress-strain parameters via the Hardening Soil Model was used for a finite element implementation of settlement analysis of strip footings under several set-ups which included: strip footings on homogeneous soil, strip footings on soils with a shallow water table, and closely-spaced strip footings. With respect to its stiffness behavior, the Hardening Soil model involves a power law formulation for stress-dependent stiffness, similar as the one used in the Duncan and Chang model. In fact, the model shows correspondence with the Duncan-Chang model regarding its hyperbolic stress-strain response when simulating a standard drained triaxial test. The study shows that the Duncan and Chang hyperbolic parameters may be converted to Hardening Soil model parameters. Because of this, settlement of soils under the strip footings were modeled more accurately by incorporating three input stiffness parameters corresponding to the triaxial loading stiffness (E50), the triaxial unloading-reloading stiffness (Eur), and the oedometer loading modulus (Eoed). The study also reveals that the Hardening Soil model has apparent differences with the commonly used Mohr-Coulomb model. This can be attributed to the fact that the Mohr-Coulomb model only uses a single Young's modulus and cannot distinguish between loading, unloading, and reloading. Hence, making the Hardening Soil model a more effective and accurate way of describing soil behavior.
Thesis (Master of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Soil mechanics; Shear strength of soils; Strains and stresses